Squamous Cell Carcinoma of the Oral Tongue: A Single Institution Retrospective Cohort Study from Mansoura University Hospital - Hamdy, Rasha; Halim, Amal (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Egyptian hospital–based statistics showed that head & neck carcinomas represent 18% of all cancers and mostly diagnosed at advanced stages. Our Clinical Oncology & Nuclear Medicine Department of Mansoura Faculty of Medicine serves a large rural area of the Delta region of Egypt. There is no previous study in our institution that focused on oral tongue carcinoma alone. This study aims in establishing the demographics, treatment outcome and prognostic factors of oral tongue squamous cell carcinoma (SCC).Methods: We retrospectively reviewed data of 50 cases with oral tongue SCC treated in our department from January 2014 to December 2016 to evaluate the demography, pathological characteristics, and therapeutic modalities. We estimated the survival rates during the entire follow-up period by the Kaplan–Meier method. The univariate and multivariate Cox proportional hazards analysis were performed for prognostic factors determination.Results: The median follow-up was 30 months (range: 4-45 months). The 3-year overall survival (OS) and disease-free survival (DFS) rates were 68% and 60% respectively. By univariate analysis, both advanced stages (III, IVA) and depth of invasion >0.5 cm were statistically significant as prognostic factors for 3-year DFS and OS rates. DFS rates were 34% vs. 98% for stage III and IVA vs. stage I and II respectively (p = 0.001); 52% vs. 78% for >0.5 cm vs. ≤0.5 cm depth of invasion (p = 0.003). OS rates were 36% vs. 99% for stage III and IVA vs. stage I and II respectively (p = 0.002); 52% vs. 80% for >0.5 cm vs. ≤0.5 cm depth of invasion (p = 0.001). Multivariate analysis of prognostic factors affecting 3-year DFS and OS rates confirmed the statistical significance of the same 2 factors.Conclusions: The majority of our patients were males below 60 years. Tumors were mainly found at stage III and were moderately differentiated. Vascular invasion and lymphatic permeation were uncommon. Staging and tumor invasion depth significantly affected the outcome. The 3-year OS and DFS were 68% and 60% respectively.